Resonance Frequency Analysis of Dental Implants Placed Into the Sinus Lifts: at Stage1 and Stage 2 Surgery - R. V. Somanathan; A. Šimůnek; J. Bukač; T. Brázda; D. Kopecká (Czech Dental Chamber, 2006)
Measurement of primary stability of dental implants using resonance frequency analysis is found to be a reliable and evidence based method. It is believed that a higher value indicates a better stability and so a better prognosis for the implant. This kind of relation can also be expected from implants inserted in sinus lifts. This study proves that the values with a lower amplitude by time reach a higher value and those with higher initial resonance frequency value tend to decrease to somewhat lower values. That is, the secondary stability of the implant does not depend completely on primary stability value.